Non-communicable diseases among Orang Asli of Kampung Ulu Tual - Shalihin, Mohd Shaiful Ehsan; Mohamad, S; Mustapha, S; Nabli, S; Athirah, N; Mamat, A; Mardhiah, A; Athirah, A; Mohamad, D; Anesha, Y; Aiman, A; Hasif, A; et al. (ScienceForecast Publications LLC, 2019)
Introduction: Non communicable disease is increasing in trend and becoming one of significant major global problem that involves all strata of population including the aborigines. In fact, the prevalence might be higher in this population due to lack of access for regular screening and different sociodemographic background including tendency to migrate in different areas. Methodology: This study aims to identify the prevalence of non-communicable diseases among adult population of Orang Asli in the remote area of Pahang. A cross sectional study was conducted on 20th April 2019 during community service in Kampung Ulu Tual, whereby communicable diseases had been screened. SPSS version 23 is used for statistical analysis. Associations between variables were measured. Results: Prevalence of overweight/obesity is 36.6%, hypertension is 3.3% and abnormal blood sugar is 53.3%. There is no statistical significant association between prevalence of the non-communicable diseases across age and gender. Discussion: The prevalence of overweight/obesity among Orang Asli in this region is almost similar in our national prevalence with more than half of them are prone to develop diabetes. This study proved a linear relationship between overweight/obesity, abdominal obesity and diabetes. Conclusion: These results highlight the need for urgent interventions to reduce and prevent risk factors of non-communicable diseases even in rural area of Pahang